Improving the Quality of Frozen Chicken Sempol Products Using the Six Sigma Method at UMKM Suropati Pasuruan - Putra, Muchamad Hengki Riawan; Utomo, Eko Budi; Maulana, Faris Rochman; Huda, Muhammad Saiful (PT. ELSHAD TECHNOLOGY INDONESIA, 2024)
Suropati MSME is a frozen chicken abacus producer in Pasuruan Regency. More and more competitors require compani to improve the quality of their products as a step to prevent consumers from moving to competing products. Quality problems have not been fully implemented by Suropati MSME as seen from the large number of defective products. The purpose of this study is to determine the factors that cause product defects and provide suggestions for improvements that are in accordance with the conditions of MSME so as to achieve zero defects. The method used is six sigma DMAIC (Define, Measure, Analyze, Improve, and Control) with Failure Mode and Effect Analysis (FMEA). The sigma value obtained is 2.821 while the % final yield is 81.358%. The contributing factors are man (33.33%), machine/equipment (16.67%), method (33.33%), and environment (16.67%). The proposed improvements given are additional employees, the use of alarms, the use of production equipment according to production capacity, and temporary closure of the selling place.